2023
DOI: 10.1101/2023.03.07.531620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting SERCA2 in organotypic epidermis reveals MEK inhibition as a therapeutic strategy for Darier disease

Abstract: Mutation of the ATP2A2 gene encoding sarco-endoplasmic reticulum calcium ATPase 2 (SERCA2) was linked to Darier disease more than two decades ago; however, there remain no targeted therapies for this disorder causing recurrent skin blistering and infections. Since Atp2a2 knockout mice do not phenocopy its pathology, we established a human tissue model of Darier disease to elucidate its pathogenesis and identify potential therapies. Leveraging CRISPR/Cas9, we generated human keratinocytes lacking SERCA2, which … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 104 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…Up to now, it remained unclear why these two disorders would exhibit such similar findings in biopsies that pathologists cannot consistently distinguish the diagnoses without additional clinical information, such as whether the eruption is known to be hereditary (Darier disease) or spontaneous (Grover disease). Our recent work established an in vitro model of Darier disease and demonstrated that deficiency or chemical inhibition of SERCA2 induced hyperactivation of ERK (22), which we report here as a driver of GD pathology. Further linking these disorders with distinct origins (inherited vs. acquired), some cases of GD were recently found to harbor acquired mutations in the Darier disease-linked gene ATP2A2 encoding SERCA2, a major regulator of calcium, which can activate ERK signaling in keratinocytes (43).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Up to now, it remained unclear why these two disorders would exhibit such similar findings in biopsies that pathologists cannot consistently distinguish the diagnoses without additional clinical information, such as whether the eruption is known to be hereditary (Darier disease) or spontaneous (Grover disease). Our recent work established an in vitro model of Darier disease and demonstrated that deficiency or chemical inhibition of SERCA2 induced hyperactivation of ERK (22), which we report here as a driver of GD pathology. Further linking these disorders with distinct origins (inherited vs. acquired), some cases of GD were recently found to harbor acquired mutations in the Darier disease-linked gene ATP2A2 encoding SERCA2, a major regulator of calcium, which can activate ERK signaling in keratinocytes (43).…”
Section: Discussionmentioning
confidence: 56%
“…Paradoxically, sustained B-RAF inhibition has been shown to induce activation of MEK (20, 21), which operates downstream of RAF in the mitogen-activated protein (MAP) kinase pathway, but how this signaling aberration induces the pathologic features of GD in human epidermal keratinocytes remains unknown. In recent work, we linked Darier disease to MEK and ERK overactivation (22), which led us to hypothesize that MEK hyperactivity might also fuel GD pathogenesis. Consistent with this, prior retrospective analysis of patients co-treated with MEK inhibitors, instead of B-RAF inhibitor monotherapy, failed to develop GD as a side effect (23).…”
Section: Introductionmentioning
confidence: 99%